A high-yield Streptomyces Transcription-translation toolkit for synthetic biology and natural product applications - Toh,M; Chengan,K; Hanson,T; Freemont,PS; Moore,SJ (Journal of Visualized Experiments, 2021)
Streptomyces spp. are a major source of clinical antibiotics and industrial chemicals. Streptomyces venezuelae ATCC 10712 is a fast-growing strain and a natural producer of chloramphenicol, jadomycin, and pikromycin, which makes it an attractive candidate as a next-generation synthetic biology chassis. Therefore, genetic tools that accelerate the development of S. venezuelae ATCC 10712, as well as other Streptomyces spp. models, are highly desirable for natural product engineering and discovery. To this end, a dedicated S. venezuelae ATCC 10712 cell-free system is provided in this protocol to enable high-yield heterologous expression of high G+C (%) genes. This protocol is suitable for small-scale (10-100 μL) batch reactions in either 96-well or 384-well plate format, while reactions are potentially scalable. The cell-free system is robust and can achieve high yields (~5-10 μM) for a range of recombinant proteins in a minimal setup. This work also incorporates a broad plasmid toolset for real-time measurement of mRNA and protein synthesis, as well as in-gel fluorescence staining of tagged proteins. This protocol can also be integrated with high-throughput gene expression characterization workflows or the study of enzyme pathways from high G+C (%) genes present in Actinomycetes genomes.